Transformation of Pancasila Education in The Global Era: a Study Of Twitter Usage and Student Voter Behavior - Ariani, Sinta; Patmisari, Patmisari (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to determine the effect of using Twitter/X on student voting behavior in the 2024 election. Methodology: This study uses a quantitative approach with a correlational design. The in-strument used was developed by the researcher through variable indicators of Twitter/X usage and voter behavior. The sample was taken using propor-tional sampling, and the data collection technique used a questionnaire dis-tributed to 363 students. Results: Based on the formulation of the problems raised in this study, it was found that the use of Twitter/X has a significant influence on student voter behav-ior, which can be grouped into four groups, namely rational, critical, tradi-tional, and skeptical. The results of this study indicate that student voter be-havior is dominated by the rational, as many as 147 or 40.5% of students, while as many as 59.5% still need improvement. Applications/Originality/Value: This research is important because it classifies the orientation of student vot-er behavior and uses measurements based on indicators of Twitter/X use in-cluding participation, openness, conversation, community, and connected-ness and uses indicators of voter behavior including participation in demon-strations, discussions, solidarity actions, and consolidation. From the results of this study, efforts need to be made to improve student voter behavior, which can be done through Pancasila education by improving digital literacy skills through the use of Twitter/X as a learning medium, Pancasila education learning needs to utilize Twitter/X because Twitter/X is a popular social me-dia used, and can significantly improve student voter behavior.